Diversity and vitality of tree species in the street plantations of Kryvyi Rih city - Korshikov, Ivan; Boyko, Lyudmyla; Krasnoshtan, Oleg; Suslova, Olena; Mazur, Antonina (ScienceRise: Biological Science, 2018)
The important factor of improving the ecological-esthetical role of green plantations in the city environment is a reasoned selection of tree species for greening city territories. That is why there is a necessity to study the state of green plantations in industrial cities. The aim of the work was to study the diversity of dendroflora in city plantations in green plantations of Saksagansky district of Kryvyi Rih city and to reveal decorative species of tree plantations, most resistant to conditions of the urbanized environment. The studies were conducted by the method of inventory of green plantations with defining their type, forest valuation parameters and vitality level. It was established, that the studied territories contain 49 types of tree plants that include 17 families and present 23 genera. By the number of specimens there prevail Aesculus hippocastanum L.(13,4% of the whole number of trees), Populus bolleana Louche (7,8%), Populus nigra L. (6,6%), Ulmus laevis Pall. (6,4%), Tilia cordata Mill. (6,0 %), Robinia pseudoacacia L.(4,1%). The most number of types, characterized with 7-8 points of vitality originates from the Circumboreal floristic region (almost 39% of all species that received highest vitality indices). Fast-growing species prevail in plantations of the studied region, they are 67%. The share participation of middle-growing and slow-growing species is essentially less (23% and 10% respectively). The decrease of vitality of tree plants with age depends on their growth intensity. The decrease of vitality of tree plants is most fast in slow-growing species (in the age after 30 years), and in middle- and fast-growing species after 40-50 years. So, slow-growing tree plants must not be involved into the composition of linear street plantations of the Right-bank Pridneprovie, because they are less long-lived under these conditions. The highest vitality is typical for plants in age categories 21-30 and 31-40 years (27,4% and 22,9% respectively). The most number of trees with the lowest vitality level was revealed among young plants under 10 years old. Species of genera Fraxinus L., Acer L., Populus L., Robinia L.,Ulmus L can be recommended as the most vital among street plantations